Analisis Struktur Pembangunan Gedung Bertingkat 16 Lantai Menggunakan Software Etabs V.21 pada Green Rusun Jagakarsa, Jakarta Selatan - Panca Susilo Budi Prastio; Dedy Rutama; Arief Subagyo (Jurnal Talenta Sipil, 2026)
Rapid development in urban areas, especially in South Jakarta, has led to an increased need for safe, comfortable, and space-efficient vertical housing. One solution to meet this need is the construction of Green Rusun Jagakarsa, which is designed as sustainable housing with the application of Building Information Modeling (BIM) technology. In the context of high-rise building construction, structural analysis is a crucial aspect to ensure resistance to various types of loads, especially lateral loads caused by earthquakes. This study aims to analyze the structural design of the 16-story Green Rusun Jagakarsa building using ETABS V.21 software with equivalent static analysis and dynamic analysis (response spectrum) methods. Structural modeling was performed using Autodesk Revit 2026 to produce accurate building elements before analysis with ETABS. Evaluations were conducted on important parameters such as displacement, interstory drift, base shear, and compliance with SNI 1726:2019 and SNI 2847:2019 regulations. The analysis results show that the first mode has a vibration period of 2.856 seconds with a mass participation of 79.29% in the X direction and reaching 91.08% in the Y direction up to the 12th mode. No significant horizontal irregularities were found, although there was a V.3 type vertical irregularity on the ground floor. Overall, the building structure is declared stable, strong, and meets earthquake-resistant planning standards. In conclusion, the use of ETABS and Revit has proven effective in producing accurate, efficient structural designs that comply with national standards as a reference in planning vertical construction projects in earthquake-prone areas.